The Relationship Between Student Teacher's Relationship To The V Grade V's Student's Achievement Motivation Ibtidaiyah Madrasah Darussalam Jogosatru Sukodono: Hubungan Antara Relasi Guru Siswa Terhadap Motivasi Berprestasi Siswa Kelas V Madrasah Ibtidaiyah Darussalam Jogosatru Sukodono - Dhany Aprilluto Eka Putra Dhany; Eko Hardi Ansyah (Academia Open, 2021)
This research is motivated by the low achievement motivation of students such as not doing homework on time, not doing assignments in class on time. This study uses a quantitative approach. The type of research used is correlational which aims to determine the relationship between variables, namely the relationship between teachers and students with achievement motivation. The sampling technique in this study used a saturated sampling technique, namely 30 students of class V Madrasah Ibtidaiyah Darussalam Jogosatru Sukodono. The instrument used in this study was a questionnaire. The technique used in this research data analysis is statistical technique using Pearson Product Moment correlation calculation. with the help of SPSS 17.0 software for windows. Based on the test results obtained a correlation coefficient of 0.639 with a significance of 0.001 (<0.05). In conclusion, the hypothesis is accepted, that there is a positive relationship between teacher-student relationships and achievement motivation in fifth grade students of Madrasah Ibtidaiyah Darussalam Jogosatru Sukodono. This means that the higher the teacher-student relationship, the higher the student's achievement motivation, and vice versa